Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/smll.201601949
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Organic Solar Cells Achieved by the Simultaneous Plasmon‐Optical and Plasmon‐Electrical Effects from Plasmonic Asymmetric Modes of Gold Nanostars

Abstract: The plasmon-optical effects have been utilized to optically enhance active layer absorption in organic solar cells (OSCs). The exploited plasmonic resonances of metal nanomaterials are typically from the fundamental dipole/high-order modes with narrow spectral widths for regional OSC absorption improvement. The conventional broadband absorption enhancement (using plasmonic effects) needs linear-superposition of plasmonic resonances. In this work, through strategic incorporation of gold nanostars (Au NSs) in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Compared with AuNPs and AuNRs, AuNSs are unique in their structure that consists of a central core with multibranched (tips) surface . These unique nanostructures result in a well‐defined double localized surface plasmon resonance (LSPR) peaks at 495–560 nm (core) and 650–680 nm (multibranched tips) (see Figure S2 d), which are expected to lead to strong local electromagnetic field enhancement around the branched tips and also an improved light‐scattering effect .…”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations
“…Compared with AuNPs and AuNRs, AuNSs are unique in their structure that consists of a central core with multibranched (tips) surface . These unique nanostructures result in a well‐defined double localized surface plasmon resonance (LSPR) peaks at 495–560 nm (core) and 650–680 nm (multibranched tips) (see Figure S2 d), which are expected to lead to strong local electromagnetic field enhancement around the branched tips and also an improved light‐scattering effect .…”
Section: Figurementioning
confidence: 95%
“…Figure1cs hows the UV/Vis absorption spectrum of AuNSsd ispersed in water.T he appearance of the strong resonance band of AuNSs centered at al ong wavelength of > 650 nm is due to the formation of tips, whereas the shoulder at approximately 530-550 nm is associated with the transverse plasmon mode of the cores. [16] Such AuNSs are expectedt oh ave strong local electromagnetic field enhancement aroundt he pods/tips anda lso provide excellent light scattering, [16,17] which will lead to an enhancement in LHE of the devices.T ov erify the presence of the AuNSs in the meso-porousT iO 2 ,t he photoelectrodes were characterizedu sing X-ray photoelectrons pectroscopy (XPS). Figure S1 in the Supporting Information shows the Ti 2p (a) and Au 4f spectra (b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that embedding MNPs inside the OSC devices can improve the electrical properties; this has been demonstrated through a spatially redistributed light absorption in the active layer. Sha et al reported that plasmonic effects play a key role in the enhancement of the total exciton generation and the dense exciton generation around plasmonic nanostructures providing an effective way to improve both the electrical and optical properties of OSCs …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, a relatively clear coincidence between IPCE and extinction behavior was observed, implying that the near field effect is supposed to be a dominant path for the enhanced device performance. The current devices have shown a lower PCE, however, the device performance remains a topic for future studies such as of electrical properties, proper plasmonic structures and so on .…”
Section: Discussionmentioning
confidence: 99%